Implementasi Identitas Kependudukan Digital Bagi Kaum Urban di Kecamatan Kenjeran Kota Surabaya - Dwitasari, Tarisa (Jurnal Ilmiah Tata Sejuta STIA Mataram, 2024)
This research aims to find out the implementation of digital identity for urbanites in Kenjeran sub-district because so far urbanites in Kenjeran sub-district do not have time to take care of population administration due to their work. This research uses qualitative research methods with a descriptive approach and is analyzed using the theory of Van Meter and Van Horn which states that policy implementation performance is influenced by six variables including policy standards and objectives, resources, characteristics of implementing organizations, attitudes of implementers, and the social, economic, and political environment. This research was conducted in Kenjeran Sub-district because Kenjeran Sub-district in 2023 has the largest number of urbanites in Surabaya City. The results of this study indicate that the implementation of digital identity for urbanites in Kenjeran sub-district has gone well. Urbanites in Kenjeran sub-district can directly activate digital identity in Kenjeran sub-district with the condition that they are 17 years old and above and have recorded E-KTP and bring a physical KTP and cellphone. However, the implementation of digital identity in kenjeran sub-district has obstacles in the variable standards and target activities regarding the internal application of population identity. The variable of communication is less comprehensive so that many urbanites do not know about digital identity, and the variable of social, economic, and political environment in Kenjeran sub-district is still middle to lower class so that many people are not able to operate technology properly and are not able to have tools to support the implementation of digital identity